This is slightly tricky, since sqrt(a)sqrt(b) = sqrt(ab) is only generally true for a, b >= 0.
If you thought it held for negative numbers too then you would have spurious 'proofs' like:
1 = sqrt(1) = sqrt(-1*-1) = sqrt(-1)sqrt(-1) = -1
Instead, use the definition of the principal square root of a negative number:
sqrt(-n) = i sqrt(n) for n >= 0, where i is 'the' square root of -1.
I feel slightly uncomfortable even as I write that: There are two square roots of -1. If you call one of them i then the other is -i. They are not distinguishable as positive or negative. When we introduce Complex numbers, we basically pick one and call it i.
Anyway - back to our problem:
sqrt(-50) * sqrt(-10) = i sqrt(50) * i sqrt(10) = i^2 * sqrt(50)sqrt(10)
= -1 * sqrt(50 * 10) = -sqrt(10^2 * 5) = -sqrt(10^2)sqrt(5)
= -10sqrt(5)